46.1k views
4 votes
How to solve this sum with detailed explaination​

How to solve this sum with detailed explaination​-example-1
User Kwame
by
5.5k points

1 Answer

2 votes

Answer:

A = (- 1, 0 ) and B = (4, 0 )

Explanation:

Given

y = x² - 3x - 4

To find the x- intercepts, let y = 0, that is

x² - 3x - 4 = 0

Consider the factors of the constant term (- 4) which sum to give the coefficient of the x- term (- 3)

The factors are - 4 and + 1 , since

- 4 × 1 = - 4 and - 4 + 1 = - 3, thus

(x - 4)(x + 1) = 0

Equate each factor to zero and solve for x

x - 4 = 0 ⇒ x = 4 ⇒ point B

x + 1 = 0 ⇒ x = - 1 ⇒ point A

User Andrew Sayer
by
5.1k points